IDENTIFIKASI KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA DENGAN PROBLEM BASED LEARNING - Lisna Agustina; Rizky Baroroh (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2021)
Communication skills are skills in conveying meaning in the form of ideas or information from one person to another through certain media and providing rational reasons for a statement, changing forms from verbal language into mathematical language, and illustrating mathematical ideas into descriptions. which is relevant. This study aims to describe students' communication skills with Problem Based Learning. Data collection techniques are (1) validation, (2) PBL learning, (3) pre-test and post-test of mathematics communication skills, (4) analysis of mathematics communication skills tests, and (5) observation of student activities. This research finally resulted in the identification of students' communication skills based on indicators of mathematical communication skills, namely (a) Connecting real objects, pictures and diagrams into mathematical ideas, (b) Explaining ideas, situations and mathematical relations, in writing, (c) Stating everyday events. day in language or mathematical symbols. The identification stage is clarified in the category Very good, good, enough, not enough, not very bad. This research was conducted at SMP Negeri 1 Sipirok. To identify the increase in students' mathematical communication skills in every aspect, the t test was carried out. Based on the students' answers. The results showed that the students' mathematical communication skills with Problem Based Learning increased significantly by the value of t = 3.896 while t table = 1.685 so it could be concluded that the students' mathematical communication skills with Problem Based Learning were better.